Pelayanan Mobil Yan Starpa dalam Pembayaran Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB P-2) - Luh Putu Dinda Yunita; Nyoman Diah Utari Dewi; Luh Riniti Rahayu (Penerbit Goodwood, 2023)
Purpose: to describe the quality, factors that hinder and efforts that can be made to improve service quality. Research methodology: The method used in this research is descriptive qualitative research method. Results: The results showed that starpa car services in the payment of rural and urban land and building taxes (PBB P-2) have not been effective in terms by martini and lubis of three approaches, namely the source approach (resource approach), process approach (process approach) and goal approach (goal approach). ) due to the lack of facilities and infrastructure that are used as well as human resources that are reliable enough to operate all existing applications on starpa cars and an inadequate internet network for services to remote villages. Efforts that must be made to increase the effectiveness of starpa car services in paying land and building taxes in rural and urban areas (PBB P-2) are to add infrastructure and increase human resources that are reliable enough to be able to use existing applications in starpa car services. Limitations: This research is still analyzed descriptively and only uses a few informants. Contribution: This research can be used as evaluation material, input and suggestions in making a policy in an effort to improve starpa car services.